Bargaining, Mortgage Financing, and Housing Prices. Issue 3 (1st July 2018) - Bian, Xun; Lin, Zhenguo; Liu, Yingchun
Abstract : Bargaining and mortgage financing have been extensively studied. However, they have only been studied separately. This paper is the first to embed financing into a bargaining model. First, we show that financing creates new ground for trading. In contrast to conventional wisdom, our model shows a buyer does not have to value a property more than its seller for a mutually beneficial trade to exist, and transaction prices are not bounded by the buyer's and seller's valuations. Second, our results show that when financing is omitted in a bargaining model, the total gain from trade is incorrectly defined, and price is thus miscalculated. Third, our model can be used to analyze many commonly used financing arrangements in real estate, such as an assumable loan, seller financing, and seller-paid closing costs.